2021
DOI: 10.3390/su132313110
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Characterization of Microplastics in Coastal Fish around the Eastern Coast of Thailand

Abstract: Marine microplastic has been in the limelight recently. This study aimed to describe microplastic types ingested by 274 fish from Thailand’s eastern coast in 2020 and to compare the microplastic content among different feeding traits. The microplastics in the gastrointestinal tracts and gills were extracted, analyzed, and identified using FT-IR spectroscopy. Approximately 13.14% of the total specimen ingested microplastics, with an average of 0.14 items per individual. The detection frequency of microplastics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 69 publications
2
8
0
Order By: Relevance
“…36% respectively. The results of this study align with Phaksopa et al (2021), that the most commonly found microplastic polymers in pelagic and demersal fish were PET, with a percentage of 83.33% and 66.67%, respectively. PET is the primary material for making ropes, beverage containers, synthetic fibers, and food containers.…”
Section: Microplastic Characteristicssupporting
confidence: 90%
See 1 more Smart Citation
“…36% respectively. The results of this study align with Phaksopa et al (2021), that the most commonly found microplastic polymers in pelagic and demersal fish were PET, with a percentage of 83.33% and 66.67%, respectively. PET is the primary material for making ropes, beverage containers, synthetic fibers, and food containers.…”
Section: Microplastic Characteristicssupporting
confidence: 90%
“…A study by Nasution (2021) found fiber microplastic in Padang Beach with a percentage of 95%. Fiber microplastic was also found in the study by Phaksopa et al (2021) on microplastic in fish around the east coast of Thailand, with a percentage of 83.33% in pelagic fish and 88.89% in demersal fish. The microplastic polymer type in fish and water samples is shown in Figure 7.…”
Section: Microplastic Characteristicssupporting
confidence: 59%
“…3 The microplastics content in cat food under dry conditions The correlation between microplastic A and B detection in cat food = 72.5% with statistically significant p < 0.001 using each group having 50 cases. In the case of a wet particle of cat foods, fibers dominated, followed by film, rod, and pellets of microplastics [10,11]. This finding indicated that the pelagic has a higher risk of exposure and microplastic ingestion in relatively small amounts in domestic pet animals like cats and dogs.…”
Section: The Experimentsmentioning
confidence: 96%
“…The study conducted on the microplastics in coastal fish in Thailand by Phaksopa et al 2021 also highlighted higher microplastics ingestion by pelagic fish compared to demersal fish, and only polyamide was found in demersal fish due to the tendency of polyamide to sink and settle with higher density. The buoyancy force induced by the microplastic density can lead to variations in the microplastics ingested by demersal and pelagic fish [8]. The effect of the feeding habits of fish on microplastic pollution and abundance has also been discovered.…”
Section: Microplastics In Fishmentioning
confidence: 99%
“…The occurrence and abundance of microplastics in the water and sediments of marine and aquatic environments have been widely studied [4][5][6]. In recent years, a lot of studies have also focused on microplastic contamination in living biota, including fish, bivalves, crustaceans, and other vertebrates, to study the abundance and accumulation of microplastics within the organisms, including the gastrointestinal tract and other tissues or organs [7][8][9]. The ecotoxicological effects of microplastics on these organisms through microplastic ingestion include oxidative stress, neurotoxicity, and genotoxicity, which affect their life functions and survival.…”
Section: Introductionmentioning
confidence: 99%